Identification of genetic loci that contribute to Campylobacter resistance to fowlicidin-1, a chicken host defense peptide - Hoang, Ky V.; Wang, Ying; Lin, Jun (Frontiers in Cellular and Infection Microbiology, 2012)
Antimicrobial peptides (AMPs) are critical components of host defense limiting bacterial infections at the gastrointestinal mucosal surface. Bacterial pathogens have co-evolved with host innate immunity and developed means to counteract the effect of endogenous AMPs. However, molecular mechanisms of AMP resistance in Campylobacter, an important human food borne pathogen with poultry as a major reservoir, are still largely unknown. In this study, random transposon mutagenesis and targeted site-directed mutagenesis approaches were used to identify genetic loci contributing Campylobacter resistance to fowlicidin-1, a chicken AMP belonging to cathelicidin family. An efficient transposon mutagenesis approach (EZ::TNTM <KAN-2> Transposome) in conjunction with a microtiter plate screening identified three mutants whose susceptibilities to fowlicidin-1 were significantly increased. Backcrossing of the transposon mutations into parent strain confirmed that the AMP-sensitive phenotype in each mutant was linked to the specific transposon insertion. Direct sequencing showed that these mutants have transposon inserted in the genes encoding two-component regulator CbrR, transporter CjaB, and putative trigger factor Tig. Genomic analysis also revealed an operon (Cj1580c-1584c) that is homologous to sapABCDF, an operon conferring resistance to AMP in other pathogens. Insertional inactivation of Cj1583c (sapB) significantly increased susceptibility of Campylobacter to fowlicidin-1. The sapB as well as tig and cjaB mutants were significantly impaired in their ability to compete with their wild-type strain 81-176 to colonize the chicken cecum. Together, this study identified four genetic loci in Campylobacter that will be useful for characterizing molecular basis of Campylobacter resistance to AMPs, a significant knowledge gap in Campylobacter pathogenesis.